Processible polyacid doped polyaniline composites: Application for charge storage devices - Gupta B.; Prakash R. (My University, 2025)
Processible polyaniline (PANI) composites with a polyacid (polyacrylic acid, PAA) are synthesized and studied for their structural, electrical and electrochemical properties. The material is used for the first time for development of electrochemical capacitor. The processible conducting composites have been prepared by mixing the polyaniline and polyacrylic acid in various weight percentage from 20 wt.% to 90 wt. % (of polyaniline) under vigorous stirring and sonication conditions. Self-standing films of these electroactive and homogeneous composites were obtained by solution casting method. A significant improvement in processibility, crystallinity and stability was observed in the composites having PANI up to 90 wt.% of total content. However, the electrical conductivity decreased remarkably as the percentage of PANI decreased in the composites. The composite having 60 wt.% PANI in PAA showed very interesting structural property as it is found to be highly crystalline with orthorhombic crystal system and cell parameters as a = 5.93 Å, b = 7.57 Å and c = 10.11 Å. The composites are used for the development of electrochemical capacitors. The 60 wt.% PANI-PAA composite showed highest capacitance amongst all the composites and used as an active material for development of an electrochemical capacitor using a parallel plate assembly. © 2009 Elsevier B.V. All rights reserved.